Critical analysis of factors affecting the efficiency of nutrition therapy teams. (August 2021) - da Silva, Thales Antônio; Gomes, Mel Mariá Assunção; Generoso, Simone de Vasconcelos; Correia, Maria Isabel Toulson Davisson
Summary: Background: Nutrition therapy (NT), defined as the provision of oral, enteral, or parenteral nutrition, should be considered a part of the holistic approach to patient care, while quality assessment of its practices is crucial. The present study aimed to identify variables capable of explaining the reason behind compliance of NTTs with the regulatory requirements. Methods: A cross-sectional study focused on assessing the quality of nutritional therapy practices among NTTs who previously stated to be able to comply with requirements of the Brazilian law versus those who were not able to meet these demands. Hospitals were classified as A (teams that had previously reported to be able to meet the requirements) and B (those unable to comply with them). The study was approved by the ethics committees of all participant institutions. Results: Twenty six hospitals met the inclusion criteria. The main hospital features, such as size, classification, service type, and percentage of hospitals providing NT were similar. Hospitals differed on the median number of patients undergoing NT per week: in group B (41.0; IR = 28.0–58.0) and group A (11.0; IR = 5.0–48.0) (p < 0.05), but there were no differences regarding personnel expertise. Both hospital groups had low quality control of the NT processes. Conclusion: Lack of quality assurance is responsible for the inadequate services in both type of institutions.